POTENSI PENGEMBANGAN WISATA HALAL DALAM MENINGKATKAN EKONOMI MASYARAKAT (Studi Objek: Wisata Halal Kebun Kurma Desa Karanglo Sukorejo Pasuruan) - Sukamto, Sukamto; Farida, Alimatul; Fahmul Iltiham, Muhammad; Solichah, Mar'atus (Al-Maqashid: Journal of Economics and Islamic Business, 2023)
The tourism industry plays an important role in the global economy as it is considered as one of the contributing factors to employment growth and economic growth in any country. In Karanglo Sukorejo Village, Pasuruan, there are tours where the majority of the people are Muslim, so there is a need for an understanding of tourism in accordance with sharia rules and principles. Therefore, researchers conducted research with the title "The Potential for Development of Halal Tourism in Improving the Community's Economy (Study Object: Halal Tourism of Dates Gardens, Karanglo Sukorejo Village, Pasuruan). The purpose of this study is first to explore the potential for developing halal tourism in date plantations and secondly the impact of developing halal tourism on date plantations in improving the economy. community economy. The type of research is qualitative research using descriptive methods. While the research tools used by researchers in this study were observation, interviews and documents. From the results of the study it is known that the existence of halal tourism in date palm plantations has a positive impact on the economy of the local community because the development of this halal tourism area opens up job opportunities and also creates new jobs, especially for local communities.